«What the hell am I doin’ here? I don’t belong here!»..L’antropologa nei contesti di asilo/accoglienza tra marginalità, fraintendimenti, negoziazioni e non-intenzionalità. Riflessioni a partire da un’esperienza professionale - Silvia Pitzalis (Archivio Antropologico Mediterraneo)
Since the so-called ‘migratory crisis’ (2015) in Italy, anthropological interest in extra-academic fields related to the care of asylum seekers and refugees has gained a crucial relevance, igniting intense debates within the discipline. However, despite this openness, anthropology in these contexts remains a ‘misunderstood knowledge’ subject to ambiguous and dangerous interpretations concerning the tools, objectives and solutions it can produce. The consequent operation of de-construction of anthropological knowledge, with often essentialising drifts, is one of the most unintended and unfortunate results that the anthropologist working in these contexts has to deal with, often having to manage real ‘disciplinary’, professional, ethical and existential crises. Through the exposition of a professional experience within the asylum/reception system, I will show how, although significant, this openness can lead to real epistemological, deontological, and methodological pitfalls that go beyond the anthropologist's intentions.